Integrated networking, caching, and computing - Yu, F. Richard; Huang, Tao (Telecommunications engineer); Liu, Yunjie (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2018)
This book features the major research advances on integrated networking, caching, and computing. Information-centric networking-based caching is one of the promising techniques for future networks. The cloud computing paradigm has been widely adopted to enable convenient, on-demand network access to a shared pool of configurable computing resources. In addition, fog/edge computing is proposed to deploy computing resources closer to end devices. From the perspective of applications, network, cache and computing are underlying enabling resources. How to manage, control and optimize these resources can have significant impacts on application performance--
Includes bibliographical references and index.
CSE
Keywords: Cloud computing; Computer networks; Computer science